Jejunal Perforation Following Blunt Abdominal Trauma; a Case Report - Akhgar, Atousa (Adv J Emerg Med, 2017)
INTRODUCTION: The possibility of intestinal injury for all patients presenting to emergency department (ED) with blunt abdominal trauma, despite minimal physical signs should be considered. To highlight the patient management, hear, we report a case of hollow viscus injuries resulting from blunt abdominal trauma referring to a teaching hospital in Tehran, Iran. CASE PRESENTATION: A 30-year-old man presented to the ED after “falling into a hole” with his back and had direct blunt abdominal trauma by a heavy bag of cement. In physical examination, there was a mild abdominal tenderness on right upper quadrant. On bedside ultrasonography, there was small free fluid in his Morison’s pouch without hypotension. So abdominal CT scan was performed which revealed free fluid in pelvic, perihepatic, and perisplenic spaces. Mural hematoma of proximal part of jejunum with mural wall hypodensity in mid jejunal loop were also revealed. The patient underwent surgery, and there was damage to the colon serosa and jejunal perforation which was primarily repaired. CONCLUSION: The presented case highlights the importance of obtaining history and physical exam and paying attention to the nature and mechanism of injury. Emergency physicians should be aware of hollow viscus injury in traumatic patients. Any delay in diagnosis and operative management are associated with an increase in mortality.